PRODUÇÃO DE AMILASES POR Aspergillus niger: POTENCIAL DE APLICAÇÃO NA HIDRÓLISE DO AMIDO GRANULAR DA BATATA-DOCE - Pereira, Carla Rubiane (2015)
The world`s energy matrix is still mainly based on the use of fossil fuels, which present major problems such as emission of pollutant gases, as well the fact of that fossil fuels are limited source of energy. Faced with this problem, there is the need for studies related to the production of biofuels from renewable and clean raw materials. However, conventional processes of enzymatic starch hydrolysis for ethanol production present high production costs associated with the use of enzymes and have large energy demand, for starch gelatinization at high temperatures. Alternatively, the granular starch hydrolysis process makes the gelatinization of the starch unnecessary and reduces the energy required, showing economic advantages. The aim of this study was establish the optimal conditions for amylase production by Aspergillus niger, using sweet potato peel as substrate. Additionally aimed characterize biochemically the enzymes produced and verify its application potential in the granular starch hydrolysis process of sweet potato. For that were used as tools the statistics Central Composite Design Rotational (CCRD) applicable to Response Surface Methodology (RSM). The culture conditions that resulted in the highest amylase levels by A. niger were a substrate concentration of 2%, pH of medium 6.0 and cultivation time of 6,5 days, corresponding to 214.28 U mL?¹. The amylase produced with sweet potato was more active at 60ºC, in pH 4.5. In addition, it was stable over a wide pH range and at its optimal temperature. The hydrolysis conditions that resulted in the highest glucose levels were 37 hours of reaction, 50ºC, pH 4.0 and enzyme dosage of 31.25 U g?¹ of substrate. Under these conditions, a high yield of glucose from sweet potato starch hydrolysis was obtained, corresponded to 78.33%. This study therefore demonstrate the potential of A. niger to produce amylases in the presence of sweet potato, a little explored residue. In addition, the high glucose levels observed opens up new possibilities for making the production of ethanol from sweet potato economically viable.